An application of the tourist test to Colombian merchants - Carlos A. Arango-Arango; Yanneth Rocío Betancourt-García; Manuela Restrepo-Bernal (Latin American Journal of Central Banking (LAJCB), 2022)
As in many developing economies, cash is still widely used in Colombia, even among merchants who accept payment cards. Indeed, 60% of these merchants use dissuasive strategies to make their clients pay with cash. This paper presents estimates of merchant card fees that are optimal according to the Tourist Test, so that merchants are indifferent between being paid with cash or cards. We find the estimates are far below the rates that the industry charges because of the low marginal costs of cash and the incentives that sales-tax evasion-a common practice in many developing economies-adds to its promotion. Moreover, we find that reductions in cash usage may lead to an increase in optimal merchant card fees due to scale effects. The results show that the Tourist Test should be used as a guideline for regulators but ought to be complemented with a broader analysis of the industry.
Keywords: D23; D40; G20; G21; G28; E41; E58; 330; Cash; Debit and credit cards; Merchant card fees; Merchant interchange fees; Tourist test